2012
DOI: 10.1115/1.4005793
|View full text |Cite
|
Sign up to set email alerts
|

Chip Flow and Scaling Laws in High Speed Metal Cutting

Abstract: Chip formation in machining plays an important role in the cutting process optimisation.Chip morphology often reflects the choice of cutting conditions, the tool wear and by consequences the integrity of the machined surface and tool life. In this study, photographs of the chip morphology during high speed machining of a middle hard steel (C20 similar to AISI1020} are taken by using a ballistic setup. From these recordings, the evolution of the chip morphology is presented and analysed in terms of cutting cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…In the study [ 23 ], a high-speed camera was used to analyze the morphology of chip formation in the cutting process, the study was additionally confirmed with an analytical model and an inconsiderable influence of the cutting speed change on the geometric features of the chip. On the other hand, Guo et al [ 24 ] presented a method of using a high-speed camera to analyze the dynamics of flow, deformation fields and chip formation in the process of sliding and cutting H02 bronze.…”
Section: Introductionmentioning
confidence: 96%
“…In the study [ 23 ], a high-speed camera was used to analyze the morphology of chip formation in the cutting process, the study was additionally confirmed with an analytical model and an inconsiderable influence of the cutting speed change on the geometric features of the chip. On the other hand, Guo et al [ 24 ] presented a method of using a high-speed camera to analyze the dynamics of flow, deformation fields and chip formation in the process of sliding and cutting H02 bronze.…”
Section: Introductionmentioning
confidence: 96%
“…According to measurements reported in [24,42,44,39], this ratio is in the range 2 < A < 20 depending on the workpiece material (e.g. A ≈ 5 for steel, A ≈ 10 for copper in [42], and A ≈ 20 for aluminum in [24]).…”
Section: State-dependent Delay Modelmentioning
confidence: 99%
“…Whereas τ is the regenerative delay, which is now equal to the rotation period and can be expressed with the angular velocity Ω of the workpiece: τ = 2π/Ω. Experiments show [24,39] that the chip thicknessh(t, θ) along the rake face (also called the deformed chip thickness) is proportional to the shifted uncut chip thickness h(t + θ) (also called undeformed chip thickness):h(t, θ) = Ch(t + θ), where 1 < C < 10 is a constant depending primarily on the workpiece material and the rake angle. Thus,…”
Section: Distributed-delay Modelmentioning
confidence: 99%
See 2 more Smart Citations